Communication and resolution programs expose hard-to-hear truths - Hickson, Gerald B.; Boothman, Richard C.; Krumm, Alice M.; Wyatt, Ronald (Frontiers in Health Services, 2025)
Communication and Resolution Programs' (CRP) favorable impact on professional liability claims continues to draw attention, but because they are deliberately aligned to advance the health system's mission rather than amelioration of litigation exposure, CRPs stand a better chance of delivering durable healthcare improvements than traditional responses to patient harm. CRP adherents employ focused investigations overseen by their own patient safety leader in order to engage patients with a principled response following unintended clinical outcomes. Focused on safety and unencumbered by litigation delays, CRP investigations are more apt than traditional responses to lay bare patient safety risks including professionalism challenges. Leaders, however, must be prepared to embrace and address hard-to-hear truths about dysfunctional systems or disruptive humans that threaten outcomes of care or clinical staff wellbeing.